Differential relations among expectancy, task value, engagement, and academic performance: The role of generation status - Edwards, Ordene V.; Dai, Ting (Frontiers in Education, 2023)
We investigated differences in domain-general expectancy, value, and engagement in school by generation status and how the relationship among these constructs and academic performance differ by generation status. A total of 573 college students enrolled in introductory psychology courses participated in the study. We discovered that expectancy differed significantly by generation status, with first-generation college students (FGCS) reporting higher expectancy than continuing-generation college students (CGCS). There were no differences in task value. Multigroup structural equation modeling revealed that the effect of expectancy-value motivation on behavioral engagement was similar across groups, but its effect on cognitive engagement was greater for the FGCS than for the CGCS. For both groups, expectancy impacted academic performance via behavioral engagement. Finally, neither expectancy-value motivation nor cognitive engagement directly predicted academic performance for either group. The findings have important theoretical and practical implications.